2005
DOI: 10.1099/ijs.0.02989-0
|View full text |Cite
|
Sign up to set email alerts
|

‘Candidatus Mycoplasma haematoparvum’, a novel small haemotropic mycoplasma from a dog

Abstract: A novel small haemoplasma was detected following cytological examination of blood smears from a splenectomized dog with haemic neoplasia. The 16S rRNA and rnpB genes of the organism were partially sequenced and a phylogenetic tree constructed. The organism was most closely related to the small feline haemoplasma, 'Candidatus Mycoplasma haemominutum' (94 % 16S rRNA gene nucleotide sequence identity; 75 % rnpB) and was only distantly related to Mycoplasma haemocanis (78 % 16S rRNA gene nucleotide sequence identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 16 publications
0
49
0
Order By: Relevance
“…A total of 147 dogs with at least one laboratory abnormality (leucopenia, thrombocytopenia, pancytopenia, or anemia) were tested, resulting in 2 (1.4%) positive samples for M. haemocanis and 11 (7.5%) for 'Candidatus M. haematoparvum'. However, the sequenced PCR amplicons of 'Candidatus M. haematoparvum' were only 85% similar to the 'Candidatus M. haematoparvum' described by Sykes et al (2005), but showed 96% homology to M. haemofelis and 96% to M. haemocanis. Results suggested that, although amplified by a standard 'Candidatus M. haematoparvum' PCR protocol, this particular species of hemoplasma is phylogenetically closer to M. haemocanis than to 'Candidatus M. haematoparvum'.…”
Section: Companion Animalsmentioning
confidence: 99%
“…A total of 147 dogs with at least one laboratory abnormality (leucopenia, thrombocytopenia, pancytopenia, or anemia) were tested, resulting in 2 (1.4%) positive samples for M. haemocanis and 11 (7.5%) for 'Candidatus M. haematoparvum'. However, the sequenced PCR amplicons of 'Candidatus M. haematoparvum' were only 85% similar to the 'Candidatus M. haematoparvum' described by Sykes et al (2005), but showed 96% homology to M. haemofelis and 96% to M. haemocanis. Results suggested that, although amplified by a standard 'Candidatus M. haematoparvum' PCR protocol, this particular species of hemoplasma is phylogenetically closer to M. haemocanis than to 'Candidatus M. haematoparvum'.…”
Section: Companion Animalsmentioning
confidence: 99%
“…In small animals, multiple hemoplasma species have been characterized, including feline hemoplasmas such as Mycoplasma haemofelis, 'Candidatus Mycoplasma haemominutum' and 'Candidatus Mycoplasma turicensis' [5,17,18], and canine hemoplasmas such as Mycoplasma haemocanis and 'Candidatus Mycoplasma haematoparvum' [8,15]. M. haemofelis induces more severe clinical symptoms in the feline host than 'Candidatus M. haemominutum' [2,7], and 'Candidatus M. turicensis' has been reported to be a similarly weak pathogen [3].…”
mentioning
confidence: 99%
“…Various hemoplasmas have been detected in other animals [12,13,18], and pathogenic differences among them have been reported [2,3,14]. The phylogenetic analysis revealed that both 'Candidatus M. haemovis' and M. ovis belong to the same clade, which contains lower pathogenic species that infect other animals.…”
mentioning
confidence: 99%